Physiological responses of skilled players during a competitive wheelchair tennis match - Roy, J. L. P.; Menear, K. S.; Schmid, M. M. A.; Hunter, G. R.; Malone, L. A. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to determine heart rate (HR, b/min) response during competitive match play of 6 men who were skilled wheelchair (WC) tennis players. Each participant completed an arm crank ergometer test that measured HR via a telemetry device and O2 via open circuit spirometry from rest until fatigue (O2peak). Each athlete participated in 2 competitive singles matches during which HRs were recorded in 5-second intervals and O2 was estimated using the corresponding HR values recorded during the arm ergometer tests. Data analysis revealed an average playing intensity of 69.4 ± 8.9% of HRpeak and 49.9 ± 14.5% of O2peak. In conclusion, it is recommended that skilled adult WC tennis players perform off-court aerobic conditioning as part of their training program, because the intensity of a competitive WC tennis match is sufficiently high enough to stress the cardiovascular system.